Influence of tire temperature conditions on the capacity of quarry dump trucks operated in JSC "CC Kuzbassrazrezugol" - Kulpin Alexander (EDP Sciences, 2021)
More than 50-60% of minerals in Russia and the CIS countries are mined in an open-pit or in mining quarry, as it is the most economical and productive. JSC "CC Kuzbassrazrezugol" ranks second in terms of total coal production among the regions of the Russian Federation and first in Kuzbass. Quarry dump trucks are the main mode of technological transport when transporting mined rock. An important task facing road transport is to reduce the cost of transported products. The components of the costs include fuel, tires, maintenance and repair, maintenance of roads and others. It is possible to reduce tires costs by controlling tires life. Most often, thermal damage causes the emergency decommissioning of tires. It is possible to maintain the optimal temperature regime of quarry dump truck tires with the help of operating modes such as load capacity utilization factor and speed, as well as operating conditions such as ambient temperature and longitudinal slope of the road. In turn, the performance of quarry dump trucks directly depends on the operating modes. On the one hand, the growing utilization factor of load capacity and speed increase the productivity of quarry dump trucks, but at the same time this increases the temperature regime and reduces their reliability. This article proposes a methodology for determining the maximum productivity of quarry dump trucks operated in CC Kuzbassrazrezugol taking into account the temperature regime of tires.